Deficient amygdala habituation to threatening stimuli in borderline personality disorder relates to adverse childhood experiences - Bilek, Edda; Neukel, Corinne; Schmahl, Christian; Kirsch, Peter; Meyer-Lindenberg, Andreas; Tost, Heike (Biological psychiatry, 2019)
Background - Heightened amygdala response to threatening cues has been repeatedly observed in borderline personality disorder (BPD). A previous report linked hyperactivation to deficient amygdala habituation to repeated stimuli, but the biological underpinnings are incompletely understood. - Methods - We examined a sample of 120 patients with BPD and 115 healthy control subjects with a well-established functional magnetic resonance imaging emotional face processing task to replicate the previously reported amygdala habituation deficit in BPD and probed this neural phenotype for associations with symptom severity and early social risk exposure. - Results - Our results confirm a significant reduction in amygdala habituation to repeated negative stimuli in BPD (pFWE = .015, peak-level familywise error [FWE] corrected for region of interest). Post hoc comparison and regression analysis did not suggest a role for BPD clinical state (pFWE > .56) or symptom severity (pFWE > .45) for this phenotype. Furthermore, deficient amygdala habituation was significantly related to increased exposure to adverse childhood experiences (pFWE = .013, region of interest corrected). - Conclusions - Our data replicate a prior report on deficient amygdala habituation in BPD and link this neural phenotype to early adversity, a well-established social environmental risk factor for emotion dysregulation and psychiatric illness.